Antibody conjugated glycine doped polyaniline nanofilms as efficient biosensor for atrazine. (13th December 2017) - Bhardwaj, Sanjeev K; Sharma, Amit L; Kim, Ki-Hyun; Deep, Akash
Abstract: Atrazine is an important member of triazine family of pesticides. The development of its detection methods gained great attention due to the potential health risks associated with its contamination in various media including water, soil, and food. The contamination of atrazine in drinking water beyond the legal permissible limit of EPA (e.g. 3 ng ml −1 ) may cause various damages to living organisms (e.g. heart, urinary, and limb defects). In this research, we discuss the potential significance of a highly sensitive conductometric immunosensor for sensing the atrazine pesticide. To this end, electrochemical assembly of glycine doped polyaniline (PAni) nanofilms on silicon (Si) substrate was built and modified further with anti-atrazine antibodies. The herein developed immunosensor offered highly sensitive detection of atrazine with a low detection limit of 0.07 ng ml −1 . The proposed biosensor was simple in design with excellent performance in terms of its sensitivity, stability and specificity. Highlights Glycine doped PAni nanofilms have been electropolymerized on Silicon substrates. Functionality of the above thin films provides opportunity to develop an immunosensing platform. Highly sensitive and specific detection of atrazine has been realized over a wide concentration range with a LOD of 0.07 ng ml −1 . Novelty statement Atrazine is a widely used pesticide in the agriculture sector. It is highly recommended to develop simple biosensing systems for enabling the prospect of routine monitoring. The present research for the first time proposes the design of a glycine doped PAni based simple and highly effective biosensor for the atrazine pesticide. The doping of glycine has easily generated functional groups on the nano-PAni material for further convenient immobilization of anti-atrazine antibodies. The proposed sensor can be highlighted with advantages like ease of fabrication, use of environment friendly functionalization agent, specificity, wide linearity, and good sensitivity with enhanced viability.